Comparative structural and optical studies on pellet and powder samples of BaTiO3 near phase transition temperature. Issue 3 (15th February 2020) - Mishra, Vikash; Kumar, Anil; Sagdeo, Archana; Sagdeo, P.R.
Abstract: In order to investigate the possible effect of inter-granular strain on the physical properties of Barium titanate (BaTiO3 ), comparative studies have been carried out on the polycrystalline pellet and its corresponding powder samples. For this purpose, the polycrystalline pellet sample of BaTiO3 has been prepared via conventional solid-state reaction route and powder is obtained by crushing the part of the prepared BaTiO3 pellet. The comparative room temperature structural studies, temperature dependent optical and Raman spectroscopy measurements have been carried out on the prepared pellet and powder samples. Room temperature X-ray diffraction and Raman analysis confirms the presence of extra amount of strain in pellet sample compared with that of the powder sample. Temperature dependent Raman analysis also suggests the difference in the high temperature tetragonal to cubic transition temperature in both cases. Temperature dependent optical absorption properties measured in terms of Urbach energy (EU ), Urbach focus (E0 ) and Urbach relaxation clearly indicates the significant change in these quantities for both types of samples on BaTiO3 . Present results strongly reveal the difference in structural, optical and vibrational properties of BaTiO3 especially across phase transition in pellet and its corresponding powder which clearly shows the importance of inter-granular strain at the grain boundaries.